Infected Urachal Cyst in Adult - Aditya Airlangga Ekaputra; Besut Daryanto; Kurnia Penta Seputra (Fakultas Kedokteran Universitas Brawijaya, 2023)
Infected urachal cyst is one of urachal spectrum abnormalities. It usually presents in children because obliteration normally happened at early infancy. Rare case occurs in adult either can be small incidence or unrecognized symptoms until adulthood. Only small numbers of literature reported. The urachus is a tube extending from the anterior roof of the vesica urinaria to the umbilicus along the midline. The urachus is a vestigial fibromuscular structure located anterior to the fascia transversalis and posterior to the peritoneum. The presence of an embryonic urachal remnant can result in a variety of clinical complications. Due to the rarity of urachal residual disorders and the possibility of vague stomach or urinary symptoms, it is difficult to make a firm preoperative diagnosis. A 32-year-old female was referred to Saiful Anwar General Hospital after suffering abdominal pain for two months; the perineum felt the pain. There was a history of dysuria and nausea since the previous month, but no history of fever or change in bowel habits. Abdominal ultrasound showed an abscess at the anterior bladder and MRI showed an infected cyst mass in the suprapubic pointing to the left umbilical. Partial cystectomy and uterus biopsy were performed. The histopathologic result showed chronic inflammation tissue, and no malignancy was found. Misdiagnosis may lead to many complications such as progressive infection until malignancy therefore early detection of this case is important.